2020
DOI: 10.2108/zs190067
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal Effects on Innate Immune Response of a Subterranean Rodent

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…B cells and natural killer (NK) cells increase in healthy individuals ascending to high altitude 29,30 . Studies in animals support the observed decreases in Th1 cells and additionally demonstrate the migration of Th2 cells from the organs and periphery to the bone marrow 31–33 …”
Section: Effects Of Altitude On Lung Physiology Adaptation and Immune...mentioning
confidence: 88%
See 2 more Smart Citations
“…B cells and natural killer (NK) cells increase in healthy individuals ascending to high altitude 29,30 . Studies in animals support the observed decreases in Th1 cells and additionally demonstrate the migration of Th2 cells from the organs and periphery to the bone marrow 31–33 …”
Section: Effects Of Altitude On Lung Physiology Adaptation and Immune...mentioning
confidence: 88%
“… 29 , 30 Studies in animals support the observed decreases in Th1 cells and additionally demonstrate the migration of Th2 cells from the organs and periphery to the bone marrow. 31 , 32 , 33 …”
Section: Effects Of Altitude On Lung Physiology Adaptation and Immune...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we observed a signi cant increase in the abundance of Muribaculaceae with increasing altitude, while all our samples were collected during the warmest time of the year. Previously, we showed that the high-altitude ABMRs from the same study area possess a greater innate immune response [120]. We hypothesize that the higher abundance of Muribaculaceae could have contributed to a stronger immune function in high-altitude ABMRs.…”
Section: Changes In Bacterial Taxa and Phenotypes Among The Altitudin...mentioning
confidence: 71%